The Essential Competencies in Education: An Article Content Review - Prayogi, Saiful; Asy'ari, Muhammad (Universitas Pendidikan Mandalika, 2023)
This article conducts a comprehensive content review of 20 scholarly articles published in the International Journal of Essential Competencies in Education (IJECE) between June 2022 and December 2023, focusing on the evolving landscape of essential competencies in education. Grounded in the context of Agenda 2030 and Sustainable Development Goal 4, emphasizing inclusive and equitable quality education, the study investigates the temporal evolution, emerging themes, key findings, and global perspectives within the realm of essential competencies. The content analysis reveals a dynamic shift in research themes, marked by transitioning from traditional pedagogies to innovative, technology-integrated teaching models. Authors from diverse geographical backgrounds collaborate to contribute to the discourse, emphasizing the universal relevance of essential competencies in diverse educational contexts. The emergent themes from article titles showcase a multidimensional understanding of competencies, with a particular focus on STEM disciplines and the integration of advanced teaching methodologies. Study highlights consistently underscore the positive impact of technology integration on competency development, emphasizing the transformative potential of active, student-centered approaches. The findings and implications presented contribute to the ongoing dialogue on preparing individuals for success in the 21st century, providing educators, policymakers, and researchers with valuable insights into the multifaceted nature of essential competencies in education. The collaborative and global nature of research in this field highlights the need for adaptable frameworks and strategies encompassing diverse educational landscapes.